SARS-CoV-2 and other Coronaviruses: A matter of variations - Auda, Ibtesam Ghadban; Auda, Jamela; Salih, Rajaa Hendi (AL-Kindy College Medical Journal, 2023)
Since the appearance of COVID-19 disease as an epidemic and pandemic disease, many studies are performed to uncover the genetic nature of the newly discovered coronavirus with unique clinical features. The last three human coronavirus outbreaks, SARS-CoV, MERS-CoV and SARS-CoV-2 are caused by Beta-Coronaviruses. Horizontal genetic materials transfer was proven from one coronavirus to the other coronavirus of non-human origin like infectious bronchitis virus (IBV) of avian. Horizontal genetic materials transfer was also from non-corona viruses like astroviruses and equine rhinovirus (ERV-2) or from coronavirus-unrelated viruses, like influenza virus type C. However, SARS-CoV-2 is identical to SARS-CoV and MERS-CoV. Interestingly, Wuhan city-SARS-CoV-2 is very similar to two types of bats Coronavirus in RdRp nucleotide sequence to RdRp of SARS-CoV-2 suggesting possible transmission from bats. Moreover, many genomic mutations are found in SARS-CoV-2 genomes suggesting the mutations are developed and the virus is constantly changed. The newly discovered SARS-CoV-2 has a new open reading frame (ORF) that encodes for thirty-eight amino acid peptide chains and has no similar sequence in all reported NCBI data regarding respiratory viruses. The short peptide can serve as an identification target for SARS-CoV-2 detection.